EKSPLORASI POTENSI COCOPEAT DALAM PENGEMBANGAN GEOMEMBRAN RAMAH LINGKUNGAN UNTUK PENAHAN AIR BAWAH TANAH - Syahwanti, Hezliana; Irvhaneil; Alwi, Abubakar (JMTS: Jurnal Mitra Teknik Sipil, 2026)
This study aims to explore the potential of cocopeat as an environmentally friendly alternative material for groundwater retention applications. Conventional geomembranes made of High-Density Polyethylene (HDPE) have been proven to be highly effective in controlling water infiltration; however, they present sustainability challenges due to their non-biodegradable nature. Therefore, cocopeat, a coconut husk by-product abundantly available in West Kalimantan, is investigated as an organic-based alternative material—not as a replacement for synthetic geomembranes, but as a complementary solution for groundwater conservation under specific conditions and scales of application. This research employed a laboratory experimental method involving the washing and drying of cocopeat, mixing with biodegradable resin and water, sample molding, and permeability testing using the falling head method. The results indicate that cocopeat-based geomembranes exhibit an average permeability coefficient of 3.5902 × 10⁻⁶ cm/s, which falls into the slightly impermeable (semi-impermeable) category. These findings demonstrate that cocopeat is capable of functioning as a water infiltration barrier, although its impermeability remains lower than that of synthetic geomembranes such as HDPE. With its fine porous structure, high water absorption capacity, and stable pH ranging from 5.07 to 6.5, cocopeat shows potential for use as a groundwater retention material in conservation-oriented applications, including infiltration ponds, small reservoirs, and eco-friendly drainage base layers. Furthermore, the utilization of cocopeat contributes to organic waste reduction and supports the development of sustainable, locally sourced materials in civil engineering. This study provides a fundamental basis for further research focusing on composition optimization, compaction techniques, and field-scale testing to expand the application of cocopeat as an alternative material for groundwater retention. Abstrak Penelitian ini bertujuan untuk mengeksplorasi potensi cocopeat sebagai material alternatif ramah lingkungan dalam aplikasi penahan air bawah tanah. Geomembran konvensional berbahan High-Density Polyethylene (HDPE) telah terbukti sangat efektif dalam mengendalikan infiltrasi air, namun memiliki keterbatasan dari sisi keberlanjutan karena bersifat non-biodegradable. Oleh karena itu, cocopeat yang merupakan limbah sabut kelapa dengan ketersediaan melimpah di Kalimantan Barat dikaji sebagai material alternatif berbasis organik, bukan sebagai pengganti geomembran sintetis, melainkan sebagai solusi tambahan untuk aplikasi konservasi air tanah pada skala dan kondisi tertentu. Penelitian ini menggunakan metode eksperimen laboratorium yang meliputi proses pencucian dan pengeringan cocopeat, pencampuran dengan resin biodegradable dan air, pencetakan sampel, serta pengujian permeabilitas menggunakan metode falling head. Hasil pengujian menunjukkan bahwa geomembran berbahan cocopeat memiliki nilai koefisien permeabilitas rata-rata sebesar 3,5902 × 10⁻⁶ cm/s, yang termasuk dalam kategori material sedikit kedap air (semi-impermeable). Nilai ini menunjukkan bahwa cocopeat mampu berfungsi sebagai lapisan penahan infiltrasi air, meskipun tingkat impermeabilitasnya masih berada di bawah geomembran sintetis seperti HDPE. Dengan karakteristik porositas halus, daya serap air yang tinggi, serta kestabilan pH pada rentang 5,07–6,5, cocopeat berpotensi diaplikasikan sebagai material penahan air bawah tanah untuk kebutuhan konservasi, seperti kolam resapan, embung kecil, atau lapisan dasar sistem drainase ramah lingkungan. Pemanfaatan cocopeat juga memberikan nilai tambah dari sisi keberlanjutan dengan mengurangi limbah organik dan mendukung pengembangan material teknik sipil berbasis sumber daya lokal. Penelitian ini menjadi dasar awal untuk pengembangan lebih lanjut terkait optimasi komposisi, teknik pemadatan, dan pengujian lapangan guna memperluas aplikasi cocopeat sebagai material alternatif penahan air bawah tanah.